Studies on Schismatoglottideae (Araceae) of Borneo XXII: The enigmatic Aridarum montanum refound - Boyce, P.C; Wong, Sin Yeng (Singapore Garden's Bulletin, 2013)
Aridarum montanum Ridl., a species known from a single herbarium specimen allegedly collected on Gunung (Mt) Santubong, Sarawak, Malaysian Borneo in 1909, has been refound on exposed shales in Sri Aman Division, and Sarikei Division, Sarawak, and subsequently flowered in cultivation. Morphological differences of the new collection compared with the original description and figure are catalogued and commented upon. An amended and expanded species description is provided, and the plant is illustrated in habitat, and from flowering cultivated material. Speculations on the probable location origin of Brooks’ type material are proffered.